The history and global market of oral home-care products - Juliana Jobim Jardim; Luana Severo Alves; Marisa Maltz (Sociedade Brasileira de Pesquisa Odontológica, 2009)
This literature review reports the history and the current market of oral home-care products. It provides information extending from the products used by our ancestors to those currently available, as well as on the changes in the supply and consumption of these products. Although the scientific knowledge about oral diseases has improved greatly in recent years, our ancestors had already been concerned with cleaning their teeth. A variety of rudimentary products and devices were used since before recorded history, like chewing sticks, tree twigs, bird feathers, animal bones, tooth powder and home-made mouth rinses. Today, due to technological improvements of the cosmetic industry and market competition, home-use oral care products available in the marketplace offer a great variety of options. An increase in the consumption of oral care products has been observed in the last decades. Estimates show that Latin America observed a 12% increase in hygiene and beauty products sales between 2002 and 2003, whereas the observed global rate was approximately 2%. A significant increase in the per capita consumption of toothpaste, toothbrush, mouthrinse and dental floss has been estimated from 1992 to 2002, respectively at rates of 38.3%, 138.3%, 618.8% and 177.2%. Pertaining to this increased supply and consumption of oral care products, some related questions remain unanswered, like the occurrence of changes in disease behavior due to the use of new compounds, their actual efficacy and correct indications, and the extent of the benefits to oral health derived from consuming more products.